Do Oil Price Shocks Give Impact on Financial Performance of Manufacturing Sectors in Indonesia? - Wiryono, Sudarso Kaderi; Sudrajad, Oktofa Yudha; Prasetio, Eko Agus; Setiawati, Marla (International Journal of Energy Economics and Policy, 2020)
The panel vector autoregression model is estimated using three main variables related to with profitability, financial liquidity, and financial leverage for 94 manufacturing companies from 2000 to 2017 in Indonesia. The aim is to examine the impact of oil price shocks on the ROA (profitability), CR (financial liquidity), and DER (financial leverage). The impulse reaction function of samples reveals some remarkable results. First, the response of ROA, DER, and CR appears to be consistent in many ways. Second, either Brent oil or WTI oil gives the same result for these variables. Third, financial liquidity for Indonesia manufacturing companies is not affected by the oil prices. The results obtained are robust following the GMM model in the estimation of the panel VAR. Keywords: Oil price shocks, Panel VAR, Impulse Reaction Function, GMM model JEL Classifications: L6, Q4 DOI: https://doi.org/10.32479/ijeep.9808